Any trope but you : a novel - Lavine, Victoria (Atria Paperback, 2025)
"Beloved romance author Margot Bradley has a dark secret: she doesn't believe in Happily Ever Afters. Not for herself, not for her readers, and not even for her characters, for whom she secretly writes alternate endings that swap weddings and babies for divorce papers and the occasional slashed tire. When her Happily Never After document is hacked and released to the public, she finds herself canceled by her readers and dropped by her publisher. Desperate to find a way to continue supporting her chronically ill sister, Savannah, Margot decides to trade meet-cutes for murder. The fictional kind. Probably. But when Savannah books Margot a six-week stay in a remote Alaskan resort to pen her first murder mystery, Margot finds herself running from a moose and leaping into the arms of the handsome proprietor, making her fear she's just landed in a romance novel instead. The last thing Dr. Forrest Wakefield ever expected was to leave his dream job as a cancer researcher to become a glorified bellhop. What he's really doing at his family's resort is caring for his stubborn, ailing father, and his puzzle-loving mind is slowly freezing over--until Margot shows up. But Forrest doesn't have any room in his life for another person he could lose, especially one with a checkout date. As long snowy nights and one unlikely trope after another draw Margot and Forrest together, they'll each have to learn to overcome their fears and set their aside assumptions before Margot leaves--or risk becoming a Happily Never After story themselves." --